2021
DOI: 10.1111/cup.14071
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of missing pathology specimens in dermatology

Abstract: Background: Occasionally specimen containers are received in the dermatopathology laboratory without an accompanying specimen. The consequences in this scenario can range from delay in care and inconvenience to patients to increased morbidity and even mortality. Data regarding incidence and associated characteristics of missing specimens are scant.Methods: Over a 10-year period (7 January 2010 to 7 January 2020) all cases with a missing specimen in a single academic dermatopathology laboratory and a single der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Of note, we reported six incidents of empty bottle specimens out of 25 662 total specimens. One study reported a comparable 83 empty bottle specimens from 270 754 specimens at a single academic dermatopathology laboratory 2 . Empty bottle specimens happen rarely but can lead to significant patient inconvenience and delays in care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of note, we reported six incidents of empty bottle specimens out of 25 662 total specimens. One study reported a comparable 83 empty bottle specimens from 270 754 specimens at a single academic dermatopathology laboratory 2 . Empty bottle specimens happen rarely but can lead to significant patient inconvenience and delays in care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating dermatopathology errors have focused on specific aspects of the diagnostic pathway, such as amendment rates, data entry errors, or missing pathology specimens. [2][3][4] The impact of medical errors is profound, costing the healthcare system an estimated $4-$20 billion annually, and is a leading cause of death in the United States. [5][6][7] A study of malpractice claims in pathology shows that while pathology claim frequency is low, the claim severity is high, especially in melanoma misdiagnoses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation